Pendampingan penyusunan perangkat pembelajaran proyek untuk menunjang Profil Pelajar Pancasila - Ryan Ardiansyah; Purwati Kuswarini Suprapto; Dea Diella (Universitas Hamzanwadi, 2023)
This training aims to train how to prepare project learning tools to support the development of the Pancasila Student Profile in the Curriculum for science teachers who are members of MGMP Sains in the West Region, Tasikmalaya Regency. The problems that are usually faced by science teachers in implementing project learning are in the preparation of student’s worksheets and the application of syntax, especially the syntax of essential questions. Schools with “mandiri belajar” status allow for implementing project learning in intracurricular based on basic competencies in the National Curriculum to be implemented in the classroom so that science teachers need to carry out refresher activities by participating in this training activity. In addition, the methods and techniques for implementing this project's learning model were also trained on science teachers. The methods used are training and mini-workshops. The training was held on the first day, followed by workshops on the preparation and development of project learning tools on the second day. The results or achievements of this activity are presented descriptively by showing that the ability of science teachers in compiling learning tools in the form of lesson plan and students worksheet respectively are as follows: 1) the suitability of the basic competence and the project model 89.5% and 78.9%, 2) the suitability of the project theme 92.1% and 84.2%, 3) the accuracy of the project learning syntax 68.4% and 63.2%, and 4) the suitability of the students worksheet questions 78.9% and 84.2%.